131I radiolabeled immune albumin nanospheres loaded with doxorubicin for in vivo combinatorial therapy. (6th February 2018) - Ji, Anping; Zhang, Yuanchao; Lv, Gaochao; Lin, Jianguo; Qi, Ning; Ji, Faquan; Du, Minghua
Abstract : For the purpose of providing new insights for high‐efficiency radiochemotherapy of hepatoma, a radioimmunotherapy and chemotherapy combinatorial therapy albumin nanospheres 131 I‐antiAFPMcAb‐DOX‐BSA‐NPs was designed and prepared. It was obtained in a high radiolabeling yield approximately 65% with the radiochemical purity of over 98%. The transmission electron microscope showed that the nanospheres obtained in good monodispersion with a diameter of approximately 230 nm. The doxorubicin (DOX) loading capacity of the DOX‐BSA‐NPs nanoparticles was determined to be approximately 180 μg/mg and 95.79 ± 3.89%. DOX was released gradually in 6 days. In vivo tumor‐growth inhibition experiments showed that after treating with 131 I‐antiAFPMcAb‐DOX‐BSA‐NPs for 14 days, the tumor volume decreased more obvious than that of other 2 time points and the control groups. All the results indicated that the radiolabeled immune albumin nanospheres 131 I‐antiAFPMcAb‐DOX‐BSA‐NPs could significantly inhibit the hepatoma tumor growth with the strategy of combinatorial radioimmunotherapy and chemotherapy. Abstract : A radioimmunotherapy and chemotherapy combinatorial therapy albumin nanospheres 131 I‐antiAFPMcAb‐DOX‐BSA‐NPs was designed and prepared. Treated by 131 I‐antiAFPMcAb‐DOX‐BSA‐NPs for 14 days, it could significantly inhibit the hepatoma tumor growth with the tumor volume decreasing more than 2 times than that of control group only treated with saline.